Sistem Informasi Tracer Study di Universitas Nahdaltul Ulama Lampung dengan PHP Native - Nuari Anisa Sivi; Dwi Utami; Maulana Malik Hidayatullah (Lembaga Pengembangan Kinerja Dosen, 2024)
Tracer studies are an important tool for universities to evaluate the achievement of graduate profiles, the relevance of the curriculum to the world of work, and the fulfillment of accreditation data requirements. At Nahdlatul Ulama University Lampung, the tracer study process was previously carried out manually and separately using Google Forms and spreadsheets, resulting in alumni data that was not centralized, prone to duplication, and difficult to analyze. This study aims to design, develop, and test the feasibility of an integrated web-based Tracer Study Information System at Nahdlatul Ulama University Lampung. The method used is software research and development with a Waterfall model, which includes needs analysis, design using UML, system implementation with PHP Native, MySQL, HTML, CSS, and JavaScript, and testing using Black Box Testing and user feasibility tests. The developed system provides admin and alumni login features, CRUD-based alumni data management, online tracer study questionnaire forms, data visualization dashboards using graphs, and a tracer report module equipped with filters and data export in CSV format. The Black Box testing results showed that all functions were 100% valid according to the scenario, while the feasibility test resulted in a score of 85% with a category of “Very Feasible”. Thus, the tracer study information system built is declared capable of improving the effectiveness of alumni data collection and management and supporting accreditation and quality assurance needs at Nahdlatul Ulama University Lampung.